The adoption of IFRS for SMEs in the northern sector of Ghana: A case of structural equation modeling - Peter Sappor; Francis Atta Sarpong; Rezikatu Ahmed Seidu Seini (Cogent Business & Management, 2023)
The current study investigated the adoption of IFRS for SMEs among 800 SMEs in the northern sector of Ghana. The study specifically determined the awareness level and extent of adoption of the standard. It also assessed how coercive, memetic, normative and environmental factors influenced the adoption of standards among the SMEs. It utilized an explanatory research design that adopted a quantitative approach to analyzing data and making inferences. Adapting a close-ended questionnaire, the PLS-SEM was used in analyzing the data. The study revealed that the majority of SMEs were aware of IFRS for SMEs in financial reporting to a high extent. The study further found that most SMEs did not fully comply to the IFRS for SMEs in preparing and presenting financial statements. Again, Coercive isomorphism and Environmental factors positively influenced the adoption of IFRS for SMEs among SMEs in the northern sector of Ghana. In contrast, mimetic and normative isomorphism played no significant role in the adoption process. The study further found that level of compliance positively moderates the effect of the level of Awareness on IFRS for SME adoption. Challenges associated with IFRS for SMEs (COF) positively influenced its adoption.
Keywords: 650; coercive isomorphism; environment factors; IFRS adoption; normative isomorphism; structural modeling